Budesonide Suppositories Are Effective and Safe for Treating Acute Ulcerative Proctitis - Kruis, Wolfgang; Neshta, Viacheslav; Pesegova, Marina; Alekseeva, Olga; Andreev, Pavel; Datsenko, Oleksii; Levchenko, Olena; Abdulkhakov, Sayar; Lozynskyy, Yuriy; Mostovoy, Yuriy; Soloviev, Konstantin; Dorofeyev, Andrey E.; et al. (Clinical Gastroenterology and Hepatology, 2019)
Background & Aims: Although proctitis is the most limited form of ulcerative colitis, it causes unpleasant symptoms. Topical mesalamine, the standard treatment, is not always effective. We conducted a randomized phase 2 trial to determine the efficacy and safety of 2 doses of a budesonide suppository vs mesalamine suppositories vs combined budesonide and mesalamine suppositories for proctitis. Methods: We performed a prospective, double-blind, double-dummy, multicenter trial in 337 patients with active proctitis to compare the efficacies of 4 different suppository treatments. Patients were randomly assigned to groups given 2 mg budesonide suppositories (2 mg BUS; n = 89 patients), 4 mg BUS (n = 79), 1 g mesalamine suppositories (1 g MES; n = 81), or the combination of 2 mg BUS and 1 g MES (n = 88). The study was performed from November 2013 through July 2015 at 36 study sites in Europe and Russia. The primary end point was the time to resolution of clinical symptoms, defined as the first of 3 consecutive days with a score of 0 for rectal bleeding and stool frequency. Results: The mean time to resolution of symptoms in the 4 mg BUS (29.8 days) and combination of 2 mg BUS and 1 g MES (29.3 days) groups resembled that of the standard 1 g MES treatment (29.2 days), but was significantly longer in the 2 mg BUS group (35.5 days). Furthermore, proportions of patients with deep, clinical, and endoscopic remission, as well as mucosal healing, were similar among the 1 g MES, 4 mg BUS, and combination therapy groups, but significantly lower in the group that received 2 mg BUS. No safety signals were observed, and the patients’ treatment acceptance was high (67%–85% of patients). Conclusions: In a multicenter randomized trial, we found that the efficacy and safety of 4 mg BUS in treatment of active proctitis did not differ significantly from those of 1 g MES. Budesonide suppositories offer an alternative therapy to mesalamine for topical treatment of proctitis. Clinicaltrialsregister.eu no: 2012-003362-41.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Inflammatory Bowel Disease; Mesalazine; RCT; Ulcerative Colitis